若m^2+n^2=6n-4m-13,则m^2-n^2=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 23:40:12
若m^2+n^2=6n-4m-13,则m^2-n^2=若m^2+n^2=6n-4m-13,则m^2-n^2=若m^2+n^2=6n-4m-13,则m^2-n^2=m^2+n^2=6n-4m-13m^2
若m^2+n^2=6n-4m-13,则m^2-n^2=
若m^2+n^2=6n-4m-13,则m^2-n^2=
若m^2+n^2=6n-4m-13,则m^2-n^2=
m^2+n^2=6n-4m-13
m^2+4m+4+n^2-6n+9=0
(m+2)^2+(n-3)^2=0
{m+2=0
n-3=0
∴{m=-2,n=3
m^2-n^2=4-9=-5
若m^2+n^2=6n-4m-13,则m^2-n^2=
若m^2+n^2-6n+4m+13=0则m-n=?
若|m-n|=n-m,且|m|=4,|n|=3,则(m+n)×(m+n)=几
若m-n=2 m+n=5 则M平方-N平方 的值为
一道数学题m+n/2+m-n/3=6 ,4(m+n)-5(m-n)=2
若m×m+n×n-6n+4m+13=0,则m×m-n×n=?
(m-2n)^=(m+2n)^+N,此N等于多少?
m^2+n^2=6n-4m-13,则m^2-n^2=?
m^2+4m+n^2-6n+13=0,则m+n=
若x^2+n^2—6n+4m+13=0,则m-n
若m+n=2,mn=-3,则(m-n)=
已知3m=4n,则m/m+n+n/m-n-m^2/m^2-n^2=
求m,n 以知 3m-2n=4 2m-3n=6
若(2m-n)²=3mn,求代数式n/m+4m/n-1的值
若m^2+n^2=6n-4m-13,则m^2-n^2=( )
若m^2+n^2=6n-4m-13,则m^2-n^2=()
若m^2+n^2-6n+4m+13=0,则m^2-n^2=?
已知m,n都为自然数,且m(m-n)-n(n-m)=12,求m,n的值.∴(m-n)(m+n)=1×12=2×6=3×4这步是怎么回事